Vampire knight [videorecording (DVD)] : the complete series (Viz Media ; Warner Home Video, 2011)
At prestigious Cross Academy, Yuki Cross and Zero Kiryu keep watch over the Day Class students, who are all infatuated with the beautiful, elite Night Class students. As Guardians, Yuki and Zero must also protect the secret of the Night Class - they're all vampires! Contains all 13 episodes.